Finding Junie Kim - Oh, Ellen (Harper, an imprint of HarperCollinsPublishers, 2021)
A tale based on true events follows the coming-of-age of a girl who is motivated by an act of racism at school to learn about her ancestral heritage and her grandparents' experiences as lost children during the Korean War.